(Implementation and Development of HACCP System on Food Industry in Indonesia) - Sudibyo, Agus; Esti Rahayu, Sri; Maman Rohaman, M; Neffi Ridwan, Indra; D. Sirait, Shinta; Aprianita, Nirwana; Sutrisniati, Dwi; -, Ressytustra (Warta Industri Hasil Pertanian, 2001)
Research on implementation and development hazard analysis critical control point(HACCP) system on food safety on facing international trde and globalization .the methods used was based on descriptive analysis ,that are problem identification of food safety system issue on small and medium industry (SMIS) ,selection and empowerment to SMIS training and guiding in food safety system to SMIS implementing of HACCP management system in SMIs ,food safety auditing based on food safety system to SMIs were still weak and need to be improved in terms of good manufacturing practice (GMP) facilities ,sanitation and personnel hygiene awareness ,responsibility and commitment on food safety system the food safety audit resulted that were five SMIs have met foodsafety plus requirements.